PEMODELAN CONTRACEPTIVE PREVALENCE RATE (CPR) DI SUMATERA BARAT MENGGUNAKAN PENDEKATAN REGRESI NONPARAMETRIK SPLINE - Jihad Lillah; Helma Helma (Journal of Mathematics UNP, 2021)
This study aims to identify the factors that influence the percentage of CPR and to model the pattern of the relationship between CPR and the factors thought to influence it using a nonparametric spline regression approach. The spline regression used has an optimum knot point with a minimum CGV value of three knot points. Based on the results of parameter testing, it is known that the factors that affect the percentage of CPR are the percentage of the poor people, the percentage of women aged 15 years and over with the highest education being small from junior high school, the percentage of women aged 15 years and over who are included in the workforce and the percentage of the number of family planning service posts. This nonparametric spline regression model has a coefficient of determination (R2) is  96.14%.